Some aspects of the mission policy and practice of the Church of the Province of South Africa in Ovamboland, 1924-1960 - Mallory, Charles Shannon (Rhodes University, Faculty of Divinity, Department of Divinity, 1971)
This thesis is a study that was originally inspired by the question, "What does it mean to be a Christian in rural Africa today?" While the Church needs to ask this question everywhere in the world, from experience the writer believes it is especially germane to the non-Western cultures of Africa and Asia. That experience is drawn from eight years' work among the Kwanyama tribe of Ovambos in the Ovamboland Anglican Mission. Hence, this study is confined to one rural African tribe as it came under 46 years' influence of one Christian denomination.
Keywords: Church of the Province of Southern Africa -- Namibia -- Owambo